Phytochemical and antitrypanosomal investigation of the fractions and compounds isolated from Artemisia elegantissima. (August 2014) - -Rashid, Mamoon-Ur; Ali, Saqib; Alamzeb, Muhammad; Igoli, John; Clements, Carol; Shah, Syed Qaiser; Ferro, Valerie A.; Gray, Alexander Irvine; Khan, Muhammad Rafiullah
Abstract Context: Trypanosoma brucei brucei (T.b. brucei) infection causes death in cattle, while the current treatments have serious toxicity problems. However, natural products can be used to overcome the problems associated with parasitic diseases including T.b. brucei. Objective: Artemisia elegantissima Pamp (Asteraceae) was evaluated phytochemically for its constituents and antitrypanosomal potential against T.b. brucei for the first time. Scopoletin isolated from A. elegantissima has shown better potential then the standard drug suramin, used against T.b. brucei. Materials and methods: The ethanol extract of the aerial parts of A. elegantissima was fractionated by column and preparative thin-layer chromatography into six fractions (A–F) yielding 13 compounds, these were evaluated for their antitrypanosomal activity against T.b. brucei at different concentrations. Results: Thirteen compounds were isolated from A. elegantissima: (Z)-p-hydroxy cinnamic acid, stigmasterol, β-sitosterol, betulinic acid, bis-dracunculin, dracunculin, scopoletin, apigenin, dihydroluteolin, scoparol, nepetin, bonanzin, and 3′, 4′-dihydroxy bonanzin. The fractions D–F were found to be active at the concentration of 20 µg/ml and three compounds isolated from these fractions, scopoletin (MIC ≤0.19 µg/ml), 3′, 4′-dihydroxy bonanzin (MIC = 6.25 µg/ml) and bonanzin (MIC = 20 µg/ml), were found to be highly active. Discussion and conclusion: Artemisia elegantissima was phytochemically and biologically explored for its antitrypanosomal potential against T.b. brucei. The number and orientation of phenolic hydroxyl groups play an important role in the antitrypanosomal potential of coumarins and flavonoids. The compounds 3′, 4′-dihydroxy bonanzin and scopoletin with low MIC values, hold potential for use as antitrypanosomal drug leads.